Pengaruh Metode Sorogan terhadap Minat Belajar Santri di Madrasah Diniyah Haji Ya'qub Lirboyo Kediri - Irfan Fauzan; Muhlisin (La-Tahzan: Jurnal Pendidikan Islam, 2024)
The success and failure of an education depends on the components or factors that build it. Among these components is the concept of education in which there is a process of teaching methods. An education without a clear concept will have an impact on the unclear purpose or direction and purpose of education itself. This must be considered considering that education is an activity that has a certain purpose directed at developing the individual fully. So this research aims to find out and reveal the application of the sorogan method in increasing santri learning interest, at Madrasah Diniyah Haji Ya'qubLirboyo Kediri City, East Java. From the description above, the research problem can be formulated as follows: How is the implementation of the Sorogan Method at the Haji Ya'qub Islamic Boarding School, Lirboyo, How is the Santri Learning Interest at the Haji Ya'qub Islamic Boarding School, Lirboyo, how is the influence between the Sorogan Method and the Santri Learning Interest at the Haji Ya'qub Islamic Boarding School, Lirboyo. This research is a quantitative research, correlation. The discussion is theoretical and empiric accompanied by providing analysis in accordance with providing existing analysis. With a sample size of 30 students and implementation in Madrasah Diniyah Haji Ya'qub, Pondok Pesantren Haji Ya'qub Lirboyo Kediri City, data collection using observation, interviews, documentation and questionnaires. While the data analysis technique uses the Kendall Tau formula using computer assistance Microsoft Exels and SPSS programs. The results of the study, namely: The implementation of the sorogan method is good by looking at the average of 60.633, the students' interest in learning is also good, by looking at the average of 64.267, There is a significant relationship between the implementation of the sorogan method and the students' interest in learning, that is, the better the implementation of the sorogan, the better the students' interest in learning in Madrasah Diniyah Haji Ya'qub. This can be seen from the correlation number of 0.638, this shows a significant relationship.